AJHEMO : APLIKASI KONSEP SEHAT PEREMPUAN MADURA - Farida Nurul Rahmawati; Nikmah Suryandari (UNIVERSITAS SEBELAS MARET (UNS), 2022)
Ajhemo is an everyday term that means drinking herbal medicine for the Madurese people. For Madura women, ajhemo is a habit as an effort to maintain health, fitness and household harmony for those who have a family. Ajhemo habits are carried out by Madura women since adolescence, as a consequence of the biological process of women when they first menstruate. Ajhemo habit for Madurese women continues when women experience phases of life as women, such as getting married, giving birth, after giving birth. In addition to health factors, ajhemo habits are also one way to meet the needs and demands of husbands in spousal relationships. Madurese women's habits are related to cultural factors that are inherent early on, so this causes most Madurese women to consume traditional herbs related to sexual and reproductive organs. Until now ajhemo becomes a healthy way of life that Madurese women continue to do as a body art that includes cleanliness, beauty and health. Ajhemo for women becomes a healthy way of life that lasts for generations. Ajhemo becomes a daily requirement that is believed to improve fitness arousing sexual desire and aesthetics Keywords: ajhemo, health, Madurese womenAbstrak (Bolt)Ajhemo adalah istilah sehari-hari yang berarti minum jamu bagi masyarakat Madura. Bagi perempuan Madura, ajhemo adalah kebiasaan sebagai upaya menjaga kesehatan, kebugaran dan keharmonisan rumah tangga bagi yang sudah berkeluarga. Kebiasaan ajhemo dilakukan perempuan Madura sejak masa remaja, sebagai konsekuensi dari proses biologis perempuan saat pertama kali mengalami menstruasi. Kebiasaan ajhemo bagi perempuan Madura ini dilanjut saat perempuan mengalami fase-fase kehidupan sebagai perempuan, seperti akan menikah, melahirkan, setelah melahirkan. Selain karena faktor kesehatan, kebiasaan ajhemo juga merupakan salah satu cara dalam memenuhi kebutuhan dan tuntutan suami dalam relasi suami istri. Kebiasaan perempuan Madura ini berkaitan dengan faktor budaya yang melekat sejak dini, sehingga hal ini menyebabkan sebagian besar perempuan Madura mengonsumsi ramuan tradisional yang berhubungan dengan organ seksual dan reproduksi. Hingga sekarang ajhemo menjadi cara hidup sehat yang terus dilakukan perempuan Madura sebagai seni olah tubuh yang mencakup kebersihan, keindahan dan kesehatan. Ajhemo bagi perempuan manjadi cara hidup sehat yang berlangsung turun temurun. Ajhemo menjadi keperluan harian yang dipercaya dapat meningkatkan kebugaran membangkitkan gairah seksual dan estetika. Kata Kunci:ajhemo, kesehatan, perempuan Madura